Pulmonary Tuberculosis in Household Contacts of Pulmonary Tuberculosis Patients Registered in Dots Implemented Tertiary Care Setting - EJAZ MAHMOOD AHMAD QUERISHI, AAMIR NAZIR (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Household contacts of pulmonary tuberculosis cases are the most risky group for tuberculosis infection /disease and are the easiest group to detect tuberculosis cases. Objectives: This study was undertaken to describe the frequency distribution of active pulmonary tuberculosis in household contact of patients with active pulmonary tuberculosis Setting and study design: This descriptive observational study was carried out in chest clinic of Sir Ganga Ram Hospital Lahore. Patients and Method: Contacts aged >15 years of patients registered for treatment of tuberculosis at Model Chest Clinic, Sir Gangaram Hospital, Lahore were included in the study. The patients were asked to provide three sputum specimens two spot and one morning. Demographic features like age, sex and history of the disease were collected on a standardized questionnaire. Sputum smear microscopy for AFB was carried out at Model Chest Clinic by Zeihl-neelsen method. Results: A total of 176 household contacts were investigated for active pulmonary tuberculosis. Of them 7(3.97%) out of 176 were pulmonary tuberculosis cases confirmed by microscopic examination of sputum smear by Z-N staining method. PTB was seen more in female 4(4.65%) out of 90 as compared to male 3(3.33%) out of 86. It is seen that contacts of index cases with advanced lesions on chest radiograph and positive sputum smear had active pulmonary tuberculosis, 4(5.00%) and 5(6.94%) respectively. Active PTB was found in 7(4.43%) out 158 contacts living in overcrowded houses. Out of 116 house hold contacts with no BCG scar, 5(4.41%) were cases of PTB. Conclusion: Risk of active pulmonary tuberculosis (PTB) among household contacts is significant. Far advance lesion on chest x-ray, positive sputum smear of index case, lack of BCG scar in contact and overcrowding were associated with active pulmonary tuberculosis in household contacts.